Driving T cells to human atherosclerotic plaques: CCL3/CCR5 and CX3CL1/CX3CR1 migration axes. Issue 7 (15th April 2021) - Komissarov, Alexey; Potashnikova, Daria; Freeman, Michael L.; Gontarenko, Vladimir; Maytesyan, Derenik; Lederman, Michael M.; Vasilieva, Elena; Margolis, Leonid
Abstract : T‐cell accumulation in atherosclerotic plaques contributes to plaque destabilization. We found that several chemokine receptors are differentially expressed on peripheral blood compared to plaque‐resident T cells and corresponding ligands are upregulated in plaques. These data indicate that T‐cell migration into human atherosclerotic plaques may predominantly occur via CCR5‐CCL3 and CX3CR1‐CX3CL1 interactions.